The Influence of Defects on the Structural, Optical, and Antibacterial Properties of Cr/Cu Co-Doped ZnO Nanoparticles - Arda, L.; Raad, Z.; Veziroglu, S.; Tav, C.; Yahsi, U. (ELSEVIER, 2025)
In this research, Cu/Cr codoped ZnO nanoparticles (Zn0.99-xCu0.01CrxO) were prepared using the sol-gel technique. The dopant ratio was systematically varied, ranging from x = 0.01 to 0.05 in increments of 0.01. This variation allowed for an exploration of the impact of defects on the structural, microstructural, optical, and antibacterial properties of Cu/Cr-codoped ZnO nanoparticles. Structural analysis of the Zn0.99-xCu0.01CrxO nanoparticles was conducted using X-ray diffraction. The findings confirmed the presence of a hexagonal wurtzite structure in the ZnCuCrO nanoparticles, as determined by the c/a ratios in the range of 1.6013 and 1.6039. The surface morphology, crystallite size, and nanoparticle shapes were determined through scanning electron microscopy. The nanoparticle elemental compositions were analyzed through electron dispersive spectroscopy. The optical characteristics of the samples were assessed using a UV spectrophotometer. The energy band gaps for the nanoparticles were computed, and we discussed how dopant elements and defects affected their optical properties. We determined the refractive index using five distinct models. Notably, the highest band gap was observed for Zn0.94Cu0.01Cr0.05O (E-g=3.27 eV).Positron annihilation lifetime spectroscopy was employed to investigate the defect type, defect density, and crystal quality of Cu/Cr-codoped ZnO nanoparticles. The shortest lifetime tau 1 obtained the highest value (0.181 ns) for Zn-0.97 Cu0.01Cr0.02O nanoparticles. Zn0.99-xCu0.01CrxO NPs were assessed for their antibacterial effects on E. coli (gram-negative) and S. aureus (gram-positive). Cu/Cr codoped ZnO nanoparticles show potential as materials for optoelectronic and sensor applications due to their broad band gap (Eg > 3) and high refractive index (n > 2).
Keywords: Cu/Cr codoped ZnO; Sol-gel method; Optical properties; Defects; Positron annihilation lifetime spectroscopy; REFRACTIVE-INDEX; MAGNETIC-PROPERTIES; ENERGY-GAP; FE; POWDER; Chemistry